A study of pattern of injuries and factors affecting the injury pattern among road traffic accident victims - Anil Kumar, Karmakonda; Shadan Taj, Qurat Ul Ain (International Journal Of Community Medicine And Public Health, 2020)
Background: Road traffic injuries remain a critical public health concern. The most affected are the young population. Road accidents are one of the top three reasons for deaths among the population from the age group of 5 to 44 years, globally. Road traffic injuries can be prevented by a national plan or various strategies. Methods: It is a hospital based study done on all road traffic accident cases admitted in Owaisi Hospital between April 2013 to July 2014 using a pretested, pre-designed questionnaire and collecting Medico legal case records. Data is expressed in percentages. Association between factors and severity of injuries was calculated using Chi-square test. Results: Majority of the victims had suffered grievous injury (95.29%). Majority (62.48%) had injuries involving upper limb, 52% had injuries involving multiple body regions. Majority of the times it was a sideways collision 275 (48.00%), followed by head on collision 198 (34.55%). Factors such as use of the seat belt, alcohol consumption, lighting on the road are found to be statistically significant with the severity of the injuries. Conclusions: Majority of the victims had suffered from multiple injuries (52%). The road traffic accidents can be prevented mainly putting emphasis on the use of seat belt, avoidance of consumption of alcohol by the drivers, adequate lighting on roads which can reduce the burden of occurrence of the road traffic accidents.